Applications of the GDELT project in heritage conservation: the case of the IIMA (L. Kahn) - Vergara Muñoz , Jaime; Martínez-Monedero, Miguel (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
The diffusion through social networks popularizes the architectural fact. Its visibility contributes to awakening an international sensitivity that in many cases ends with political and social decisions for the benefit of the conservation of architecture. This article addresses, as a case study, the recent demolition proposal of Louis Kahn’s IIMA, in Ahmedabad (India). On this example, it is studied how the messages that circulate in the digital media can be directed to achieve some aspect related to their conservation. The methodology of this research has been fundamentally experimental, in which different variables have been considered: the architectural reality of the building (the IIMA); the news published in different digital media; and how long the news has been active. The GDELT Project is used as a tool to analyze the communicative narratives present on the internet network.